Non-classical CH⋯O hydrogen-bond determining the regio- and stereoselectivity in the [3 + 2] cycloaddition reaction of (Z)-C-phenyl-N-methylnitrone with dimethyl 2-benzylidenecyclopropane-1, 1-dicarboxylate. A topological electron-density study. Issue 120 (19th November 2015) - Nacereddine, Abdelmalek Khorief; Sobhi, Chafia; Djerourou, Abdelhafid; Ríos-Gutiérrez, Mar; Domingo, Luis R.
Abstract : Formation of a non-classical CH⋯O hydrogen-bond involving the nitrone C–H hydrogen is responsible for the selectivity experimentally found in this non-polar zw-type 32CA reaction. Abstract : The role of the ester groups in the regio- and stereoselectivities of the zw-type [3 + 2] cycloaddition (32CA) reaction of C -phenyl- N -methylnitrone with dimethyl 2-benzylidenecyclopropane-1, 1-dicarboxylate (BCPC) has been studied using DFT methods at the MPWB1K/6-31G(d) level. The possible ortho / meta regioisomeric channels and the endo / exo stereoselective approach modes were explored and characterized. Analysis of the relative energies associated with the different reaction pathways indicates that the presence of the two CO2 Me groups in the cyclopropane ring has a remarkable effect on selectivities favouring the ortho / endo path, in good agreement with the experimental data. Inclusion of solvent effects increases the activation energy and decreases the exothermic character of both 32CA reactions but does not change gas phase selectivities. The electron localisation function (ELF) topological analysis along the most favourable ortho / endo path allows us to explain the formation of the C–C and O–C bonds through a non-concerted two-stage one-step mechanism. Non-covalent interaction (NCI) analysis of the most favourable ortho / endo transition state structure reveals that the formation of a non-classical CH⋯O hydrogen-bond involving the nitrone C–H hydrogen is responsible for the selectivity experimentally found in this non-polar zw-type 32CA reaction.